036 Tourette syndrome associated with loss of the IMMP2L gene. Issue 10 (24th September 2010) - Katuwawela, I; Rickards, H; Cavanna, A E
Abstract : Aims: Tourette Syndrome (TS) is a neurodevelopmental tic disorder with a strong hereditary component. Little is known about the role of genetic lesions in the development of TS. Methods: We provide a clinical and genetic description of a case of TS related to chromosomal translocation, along with a brief discussion and literature review. Results: An 18 year old male with TS and moderate learning disability was referred to the specialist TS clinic at the Department of Neuropsychiatry, Birmingham, for assessment and further management. Motor tics began at 11 years and vocal tics at 15. Tic-related symptoms included echolalia and palilalia. The patient also showed specific obsessive-compulsive behaviours, including excessive orderliness and rigid routines. His family history was positive for OCD and autism, but not for tics. His original karyotype analysis showed a balanced 2;7 chromosomal translocation (de-novo) of uncertain significance. Recent microarray analysis demonstrated a microdeletion of 7q31.1 containing the IMMP2L and FOXP2 genes. Conclusions: IMMP2L mutation has been reported in autism and ADHD. The association with TS has been described only once previously. However in the previous report IMMP2L inactivation was due to an inverted duplication, whereas we observed an unbalanced translocation with microdeletion, illustrating genetic heterogeneity.